How do professional development programs on comparing solution methods and classroom discourse affect students' achievement in mathematics? The mediating role of students' subject matter justifications. (December 2022) - Mok, Sog Yee; Hämmerle, Christian S.; Rüede, Christian; Staub, Fritz C.
Abstract: Comparing solution methods fosters strategy flexibility in equation solving. Productive classroom discourse such as Accountable Talk (AT) orchestrated by teachers can improve students' justifications during classroom discussions and achievement. Do students' subject matter justifications during classroom discourse mediate the effect of teachers' professional development (PD) programs focused on comparing and AT on students' mathematics achievement? We investigated whether two PD programs (comparing or comparing+AT) compared to a control group increased the number of students justifications, and whether this affected mathematics achievement (strategy flexibility, procedural knowledge, and conceptual knowledge). The study (739 9th and 10th grade students in 39 classes) had an experimental pre-post control group design. Both PD programs significantly increased students justifications compared to the control group. The results of our multilevel path models showed significant small mediation effects in the comparing+AT group on procedural and conceptual knowledge. No mediation effects were found in the comparing group. Highlights: We implemented two PDs on comparing (comp) or comp + Accountable Talk (AT). We explored multilevel mediation effects of students' justifications on achievement. Justifications were a significant mediator only for the PD comp + AT. PD comp + AT showed small mediation effects for procedural and conceptual knowledge.